Makna Rumah Bagi Masyarakat Jawa - -, Indarto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
Communities on the island of Java considers the house like a man worthy to be appreciated and respected. Respect means honoring the house occupants inside the man. Houses must be respected because it is sacred. This statement was seen when the ceremonies at the time of making the residence. Before the house started its construction, the thing to do is to give offerings as gratitude to God. Typically these offerings in the form of crops if the various types of food and pray together like a newborn baby. This traditional ceremony is performed from the ancestors of the Javanese community. Construction of the house is sacred and holy. Implementation of deve-lopment chosen by the good days are tailored to the occupants and a good day for the people in Java. Because the house as a sacred container, then the Javanese people always treat her well and always clean so that their lives are always peaceful and prosperous future free from the calamity that has adversely affected the family.Â Keywords: Houses, Sacred and Holy, Offerings, Peace and Prosperity